ANALISIS HUBUNGAN TRANSAKSI PEMBAYARAN NON TUNAI DAN HARGA BAHAN BAKAR MINYAK TERHADAP TINGKAT INFLASI DI INDONESIA - Bhirawa, Stefanus Sandi Mega; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Inflation is one of the most complicated and important economic events for a country. When inflation is at a higher than average level, it can have several detrimental effects on society. There are various internal and external factors that can affect the inflation rate. Using statistical data on inflation rate, debit card transaction volume, credit card transaction volume, and fuel oil price, this study aims to analyze the impact of non cash payment transactions and fuel prices on inflation rate. The results show that the use of debit cards in payment transactions has no significant impact on inflation in both the long run and short run. The use of credit cards also has no significant impact on inflation, both in the short run and long run. Meanwhile, the use of fuel oil has a significant impact on inflation in both the long and short run. The findings of this study provide additional insights for monetary and economic policies in Indonesia in managing non-cash transactions and fuel oil prices to maintain inflation stability.